2022
DOI: 10.1371/journal.pone.0277075
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in antenatal care utilization in Kandahar, Afghanistan: A cross-sectional analytical study

Abstract: Background Quality antenatal care (ANC) is one of the four pillars of safe motherhood initiatives and improves the survival and health of mother and neonate. The main objective of this study was to assess the barriers in the utilization of ANC services in Kandahar, Afghanistan. Methods This was a cross-sectional analytical study conducted over one year from December 2018–November 2019. Data were analyzed by descriptive statistics, Chi squared, and binary logistic regression. Results A total of 1524 women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
(53 reference statements)
0
0
0
Order By: Relevance
“…According to research in Afghanistan, only 24.5% of mothers carry out pregnancy planning and utilize antenatal services (Rahimi et al, 2022). A study conducted in the City of Debre Berhan reported different findings, which stated that mothers carrying out pregnancy planning were 2.08 times more likely to utilize antenatal services with a total of 77.1% of mothers (Tizazu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to research in Afghanistan, only 24.5% of mothers carry out pregnancy planning and utilize antenatal services (Rahimi et al, 2022). A study conducted in the City of Debre Berhan reported different findings, which stated that mothers carrying out pregnancy planning were 2.08 times more likely to utilize antenatal services with a total of 77.1% of mothers (Tizazu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) recommends that mothers make at least eight visits during pregnancy. These visits began with the first visit at 12 weeks of gestation, then at 20, 26, 30, 35, 38, and 40 weeks (Rahimi et al, 2022). Antenatal examination (ANC) is an activity carried out to prevent causes of morbidity and mortality in pregnant women and children.…”
mentioning
confidence: 99%